Altered Brain Excitability and Increased Anxiety in Mice With Experimental Colitis: Consideration of Hyperalgesia and Sex Differences - Nyuyki, Kewir D.; Cluny, Nina L.; Swain, Mark G.; Sharkey, Keith A.; Pittman, Quentin J. (Frontiers in Behavioral Neuroscience, 2018)
Crohn’s disease and ulcerative colitis are incurable lifelong inflammatory bowel diseases (IBD) with a rising worldwide incidence. IBD is characterized by diarrhea, rectal bleeding, severe cramping and weight loss. However, there is a growing evidence that IBD is also associated with anxiety- and depression-related disorders, which further increase the societal burden of these diseases. Given the limited knowledge of central nervous system (CNS) changes in IBD, we investigated CNS-related comorbidities in a mouse model of experimental colitis induced by dextran sulfate sodium (DSS) administration in drinking water for 5 days. In male and female C57BL6J mice, DSS treatment caused increased brain excitability, revealed by a decrease in seizure onset times after intraperitoneal administration of kainic acid. Moreover, both sexes showed increased anxiety-related behavior in the elevated plus-maze (EPM) and open field (OF) paradigms. We assessed somatic pain levels, because they may influence behavioral responses. Only male mice were hyperalgesic when tested with calibrated von Frey hairs and on the hotplate for mechanical and thermal pain sensitivity respectivelley. Administration of diazepam (ip, 1 mg/kg) 30 min before EPM rescued the anxious phenotype and improved locomotion, even though it significantly increased thermal sensitivity in both sexes. This indicates that the altered behavioral response is unlikely attributable to an interference with movement due to somatic pain in females. We show that DSS increases CNS excitability in response to administration of kainic acid, and increases anxiety-related behavior as revealed on the EPM and OF.